IDENTITAS KULINER DAN TANTANGAN MODERNISASI: STUDI TENTANG “BEPPA LAIYA” DI DESA KALOBBA TELLULIMPOE, SINJAI - Sudirman, Fakhriyah (STKIP Subang, 2026)
Modernization influences the way people enjoy their meals and their lifestyles, including traditional foods. This article discusses Beppa Laiya, a traditional dish from Kalobba Village in South Sinjai, which is part of the local community’s cultural identity. Qualitative research through interviews and observations shows that modernization has caused problems such as a decline in interest among the younger generation, a shift in taste toward instant foods, and a lack of people capable of making Beppa Laiya. Nevertheless, the community continues to strive to preserve it through traditional ceremonies, social activities, and adaptations to the modern market. The findings of this study emphasize that modernization is not only a threat but also an opportunity to explore new ways of preserving traditional cuisine.